2022
DOI: 10.3390/atmos13071145
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Soil N2O Emission and CH4 Uptake to N Input in Chinese Forests across Climatic Zones: A Meta-Study

Abstract: Enhanced nitrogen (N) deposition has shown significant impacts on forest greenhouse gas emissions. Previous studies have suggested that Chinese forests may exhibit stronger N2O sources and dampened CH4 sinks under aggravated N saturation. To gain a common understanding of the N effects on forest N2O and CH4 fluxes, many have conducted global-scale meta-analyses. However, such effects have not been quantified particularly for China. Here, we present a meta-study of the N input effects on soil N2O emission and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 82 publications
2
0
0
Order By: Relevance
“…S8 ). Previous studies based on a meta‐analysis [ 44 ], a conceptual model [ 29 ], and an ensemble of terrestrial biosphere model showed that atmospheric N deposition enhances natural soil N 2 O emissions [ 45 ], which was consistent with our results. Apart from the effect of atmospheric N deposition, climate change leaded to an increase of 1.6 Gg N 2 O yr −1 for soil N 2 O emissions ( Fig.…”
Section: Discussionsupporting
confidence: 92%
“…S8 ). Previous studies based on a meta‐analysis [ 44 ], a conceptual model [ 29 ], and an ensemble of terrestrial biosphere model showed that atmospheric N deposition enhances natural soil N 2 O emissions [ 45 ], which was consistent with our results. Apart from the effect of atmospheric N deposition, climate change leaded to an increase of 1.6 Gg N 2 O yr −1 for soil N 2 O emissions ( Fig.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, N addition significantly positively affected soil N 2 O emissions in three points, with similar phenomena observed in irrigated maize in a Mediterranean agroecosystem [27]. N addition tends to promote N 2 O emissions, and it has been found that among the various factors affecting soil N 2 O emissions, the amount of N application is the most decisive [28,29]. The nitrification process gradually depletes the soil of energy materials and easily decomposable organic N, so the gas emissions gradually stabilize in the later stages [30].…”
Section: Discussionsupporting
confidence: 80%